Targeting Different Pathways Using Novel Combination Therapy in Triple Negative Breast Cancer - Mir, Manzoor; Khan, Hina; Mehraj, Umar; Nisar, Safura; Bhat, Basharat; Wani, Nisar (Current cancer drug targets, 2020)
Triple negative breast cancer (TNBC) is one of the most aggressive subtype of breast cancer accounting for 15-20% of cases and is defined by the lack of hormonal receptors viz., estrogen receptor (ER), progesterone receptor (PR) and expression of human epidermal growth receptor 2 (HER2). Treatment of TNBC is more challenging than other subtypes of breast cancer due to the lack of markers for the molecularly targeted therapies (ER, PR, and HER-2/ Neu), the conventional chemotherapeutic agents are still the mainstay of the therapeutic protocols of its patients. Despite, TNBC being more chemo-responsive than other subtypes, unfortunately, the initial good response to the chemotherapy eventually turns into a refractory drug-resistance. Using a monotherapy for the treatment of cancer, especially high-grade tumors like TNBC, is mostly worthless due to the inherent genetic instability of tumor cells to develop intrinsic and acquired resistance. Thus, a cocktail of two or more drugs with different mechanisms of action is more effective and could successfully control the disease. Furthermore, combination therapy reveals more, or at least the same, effectiveness with lower doses of each single agent and decreases the likelihood of chemoresistance. Herein, we shed light on the novel combinatorial approaches targeting PARP, EGFR, PI3K pathway, AR, and wnt signaling, HDAC, MEK pathway for efficient treatment of high-grade tumors like TNBC and decreasing the onset of resistance.